A practical implementation of multifrequency widefield frequency‐domain fluorescence lifetime imaging microscopy. Issue 3 (7th January 2013) - Chen, Hongtao; Gratton, Enrico
ABSTRACT Widefield frequency‐domain fluorescence lifetime imaging microscopy (FD‐FLIM) is a fast and accurate method to measure the fluorescence lifetime, especially in kinetic studies in biomedical researches. However, the small range of modulation frequencies available in commercial instruments makes this technique limited in its applications. Herein, we describe a practical implementation of multifrequency widefield FD‐FLIM using a pulsed supercontinuum laser and a direct digital synthesizer. In this instrument we use a pulse to modulate the image intensifier rather than the more conventional sine‐wave modulation. This allows parallel multifrequency FLIM measurement using the Fast Fourier Transform and the cross‐correlation technique, which permits precise and simultaneous isolation of individual frequencies. In addition, the pulse modulation at the cathode of image intensifier restores the loss of optical resolution caused by the defocusing effect when the cathode is sinusoidally modulated. Furthermore, in our implementation of this technique, data can be graphically analyzed by the phasor method while data are acquired, which allows easy fit‐free lifetime analysis of FLIM images. Here, our measurements of standard fluorescent samples and a Föster resonance energy transfer pair demonstrate that the widefield multifrequency FLIM system is a valuable and simple tool in fluorescence imaging studies. Microsc. Res. Tech. 76:282–289, 2013. © 2013 Wiley Periodicals, Inc.